2019
DOI: 10.1007/s00417-019-04452-6
|View full text |Cite
|
Sign up to set email alerts
|

Change in visual acuity 12 and 24 months after transscleral ab interno glaucoma gel stent implantation with adjunctive Mitomycin C

Abstract: Purpose To analyze changes in best-corrected visual acuity (BCVA) after implantation of the transscleral ab interno glaucoma gel stent (XEN Gel Stent; Allergan, Dublin) in patients with open-angle glaucoma. Methods In a single-center, prospective, non-randomized study of 137 eyes with open-angle glaucoma which underwent implantation with XEN, 69 eyes underwent XEN implantation alone (group 1) and 68 eyes underwent XEN implantation and cataract surgery (group 2). BCVA (Bailey-Lovie chart, logMAR scale) was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…showed similar results in their treated POAG cases [34]. It has also been shown earlier that BCVA in eyes after TE decreases, even when taking into account (and ruling out) the known side effect of cataract formation.…”
Section: Discussionsupporting
confidence: 74%
“…showed similar results in their treated POAG cases [34]. It has also been shown earlier that BCVA in eyes after TE decreases, even when taking into account (and ruling out) the known side effect of cataract formation.…”
Section: Discussionsupporting
confidence: 74%
“…In the entire study group, XEN microstent implantation not only resulted in a reduction of IOP and necessary IOP-lowering drugs, but also had no signi cant effect on BCVA, neither in the total group of 153 eyes nor in the four subgroups analyzed. Lenzhofer et al showed similar results in their treated POAG cases [35]. It has also been shown earlier that BCVA in eyes after TE decreases, even when taking into account (and ruling out) the known side effect of cataract formation.…”
Section: Discussionsupporting
confidence: 52%
“…In the entire study group, XEN microstent implantation not only resulted in a reduction of IOP and necessary IOP-lowering drugs, but also had no signi cant effect on BCVA, neither in the total group of 153 eyes nor in the four subgroups analyzed. Lenzhofer et al showed similar results in their treated POAG cases [34]. It has also been shown earlier that BCVA in eyes after TE decreases, even when taking into account (and ruling out) the known side effect of cataract formation.…”
Section: Discussionsupporting
confidence: 52%